La gare à un mètre - Nacima Baron; Yinghua Ma (Développement Durable et Territoires)
Since the pandemy, the carrying capacity of major railway stations has been restricted to respect the distance. In Asian metropolises, a tech-driven flow management system reinforces the surveillance of travellers and help the maintenance of a top affluence in station’s buildings. In France, an attempt is made to space out travelers with less intrusive processes, such as signage and boarding protocol adaptation. A comparison between these two responses leads us to question what physical distancing does, here and there, to the practices and places of transit and to the economic injonction to densify flows in and around stations until now. Articulating the approaches of crowding science and health regulation in transit environments, the article presents a transcontinental comparison, and then questions the status of major station as post pandemic urbanism showroom.